Demokratiske samtaler i barnehagen? - Kristin Rydjord Tholin; Turid Thorsby Jansen (Nordisk Barnehageforskning, 2011)
Title: Democratic dialogues in early childhood education? Abstract: We examine what democracy-promoting practices may be in early childhood education. From an understanding of democracy as multifaceted we have studied how teachers lead planned conversations which enable children to present themselves and their interests. The issue discussed being: How can the teacher create conditions for conversations that are characterized by democracy promoting practices? The research is based on theoretical studies of democracy and conversations and video observations of conversations between teachers and children in two early childhood education institutions. The results are presented four themes: The preschool teachers’ emphasis on common experiences, their ability to make different voices distinct, show a listening participation and their daring when encountering the unexpected. Analysis shows that conversations in connections with projects can have a potential to promote practices characterized by democracy, but this seems demanding.